Permeation of Silver Sulfadiazine Into TEMPO-Oxidized Bacterial Cellulose as an Antibacterial Agent - Khattak, Shahia; Qin, Xiao-Tong; Wahid, Fazli; Huang, Long-Hui; Xie, Yan-Yan; Jia, Shi-Ru; Zhong, Cheng (Frontiers in Bioengineering and Biotechnology, 2021)
Surface oxidation of Bacterial cellulose (BC) was done with TEMPO-mediated oxidation mechanism system. After that, TEMPO-oxidized bacterial cellulose (TOBC) was impregnated with silver sulfadiazine (AgSD) to prepare nanocomposite membranes. Fourier transform infrared spectroscopy (FTIR) were carried out to determine the existence of aldehyde groups on BC nanofibers and X-ray diffraction (XRD) demonstrated the degree of crystallinity. FESEM analysis revealed the impregnation of AgSD nanoparticles at TOBC nanocomposites with the average diameter size ranging from 11 nm to 17.5 nm. The sample OBCS3, showed higher antibacterial activity against Staphylococcus aureus (S. aureus), Pseudomonas aeruginosa (P. aeruginosa) and Escherichia coli (E. coli) by disc diffusion method. The results showed AgSD content, dependent antibacterial activity against all tested bacteria and degree of crystallinity increases with TOBC and AgSD. The main advantage of the applications of TEMPO-mediated oxidation to BC nanofibers is that the crystallinity of BC nanofibers is unchanged and increased after the oxidation. Also enhanced the reactivity of BC as it is one of the most promising method for cellulose fabrication and functionalization. we believe that the novel composite membrane could be a potential candidate for biomedical application like wound dressing, BC scaffold, and tissue engineering.